The impact of the World Military Games on the COVID-19 pandemic - Winter, A. E. (Irish Journal of Medical Science, 2021)
It is clear that travel was a major factor in the rapid dissemination of COVID-19 disease. It has been proposed that Wuhan, China, was the epicentre of the pandemic. The World Military Games took place from the 18th to 27th of October 2019 in Wuhan, China. Over 140 nations with 9308 athletes participated with over 300,000 attendees, volunteers and staff [1,2,3,4]. This study examined the hypothesis that the large gathering in a pandemic epicentre was a factor in the spread of COVID-19 disease.